Respostas

  • Usuário do Brainly
2013-03-11T21:36:50-03:00

\begin{cases} x+2y-z=-4\ \ (a)\\-2x+y+3z=7\ \ (b)\\3x-2y+z=12\ \ (c) \end{cases}

 

\begin{cases} -2x+y+3z+2*(x+2y-z)=7+2*(-4)\ \ [(b)+2*(a)]\\3x-2y+z-3*(x+2y-z)=12-3*(-4)\ \ [(c)-3*(a)] \end{cases}\\

 

\begin{cases} -2x+y+3z+2x+4y-2z=7-8\\3x-2y+z-3x-6y+3z=12+12 \end{cases}

 

\begin{cases} 5y+z=-1\ \ (d)\\-8y+4z=24\ \ (e) \end{cases}

 

-8y+4z-4*(5y+z)=24-4*(-1)       [(e)-4*(d)]

-8y+4z-20y-4z=24+4

-28y=28

y=-1

 

substituindo y=-1 em (d)

5y + z = -1

5*(-1) + z = -1

-5+z=-1

z=1-+5

z=4

 

substituindo y=-1 e z=4 em (a)

x+2y-z=-4

x+2*(-1)-4=-4

x-2-4=-4

x-6=-4

x=-4+6

x=2